Diabetic ketoacidosis amongst patients with COVID‐19: A retrospective chart review of 220 patients in Pakistan. Issue 3 (24th February 2022) - Muhammad, Asim; Hakim, Muhammad; Afaq, Saima; Khattak, Farhad Ali; Shakireen, Najmush; Jawad, Muhammad; Saeed, Rabia; Haq, Zia Ul
Abstract: Objectives: To determine the frequency of diabetes mellitus and diabetic ketoacidosis and associated factors in COVID‐19‐positive patients. Background: High mortality amongst SARS‐Cov2 patients may be attributed to diabetes and diabetic ketoacidosis. Methods: A total of 220 COVID‐19 positive patients, hospitalized in North West General Hospital & Research Center, Peshawar, KP, Pakistan, from April to September 2020, were analysed using STATA 14. Patients with positive PCR were labelled as COVID‐19 positive and were included in the study. Patients with a clinical picture of COVID‐19 and negative PCR were excluded from the study. Those having ketonemia >0.6 and random blood glucose level >250mg/dl, while HCO3 (bicarbonate) ≤18, were labelled as diabetic ketoacidosis. The statistical significance level was set at p < .05. Results: A total of 220 COVID‐19 patients were admitted; 166 (75.4%) were male and 54 (24.5%) were female. The mean age in years of the patients was 55.95 (SD13.9). About 57.7% of patients had diabetes mellitus, and 15 (6.8%) patients developed diabetic ketoacidosis. Amongst those with DKA, 5 patients died during hospital admission. The use of steroids was significantly higher ( p < .001) in the DKA group compared with non‐DKA patients. Hypertension (103, 46.8%) and fever (170, 77.3%) were the most reported comorbidity and symptom respectively. Conclusion: The proportion of diabetes mellitus is high in patients with COVID‐19. Diabetic ketoacidosis is a frequent complication in this group associated with in‐hospital mortality. Steroid administration for COVID‐19 should be balanced with strict glycemic control to prevent diabetic ketoacidosis and increase hospital survival. Abstract : The newly diagnosed diabetes mellitus as a result of metabolic disturbances from COVID‐19 illnesses can lead to diabetic ketoacidosis (DKA). Our data showed that 6.82% of patients developed diabetic ketoacidosis. Usage of steroids was significantly higher while hypertension and fever were the most common reported comorbidity. We concluded that the incidence of diabetes mellitus is high in patients with COVID‐19. Diabetic ketoacidosis is a frequent complication associated with in‐hospital mortality. Steroid administration for COVID‐19 should be balanced with strict glycemic control to prevent diabetic ketoacidosis and increase hospital survival.